PENGARUH PERTUMBUHAN ASET, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN TINGKAT INFLASI TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia pada tahun 2014-2016) - Celmia Celmia; Ronny Malavia Mardani; Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe aim of this research was to know the influence of asset growth, funding decision, dividend policy, and the level of inflation to the grade of company in period 2014-2016. The population that used in this research were property and real estate which have listed on Stock Exchange. The subject of the research was determined through purposive sampling. Based on 48 companies, it obtained 11 companies which shared dividend for 4 years sequent. The data analysis that used in this research was multiple linear regression.The findings of the research showed that asset growth, funding decision, and dividend policy was positive significant to the grade of company, meanwhile, the level of inflation was not significant or negative to the grade of company. Keywords: The grade of company, asset growth, funding decision, dividend policy, the level of inflation.